Dual-texture induced significant improvement in mechanical properties of extruded ZT31 Mg alloy - Shuai Yuan; Xianhua Chen; Xiaohuan Pan; Fusheng Pan (Materials Research Letters)
Texture engineering is one of the essential strategies to regulate the mechanical properties of Mg alloys. Dual-textured Mg-3Zn-1Sn (ZT31, wt.%) extruded rod with typical fiber texture component and <0001>//ED (extrusion direction) texture component were fabricated in this work. Compared to the ZT31 extruded plate with typical basal texture (<0001>//normal direction), the ZT31 extruded rod exhibits a significant enhancement in strength while maintaining superior plasticity, achieving excellent strength and plasticity synergy. This is ascribed to the strong texture strengthening effect of the dual-textured ZT31 extruded rod, and more twin activation during deformation, which enhances the work-hardening effect, coordinates the strain along the c-axis, and facilitates homogeneous plastic deformation. This work provides a new insight into the development of high-performance Mg alloy via texture modification.